COMPARATIVE STUDY OF SOCIO-ECONOMIC VEGETABLE FARMING BETWEEN EAST JAVA AND BALI - Joko Mariyono; Putu B Daroini; Hanik A Dewi; Evy Latifah (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
This paper analyses the household and farm characteristics of vegetable farming in four regions of East Java and Bali provinces. Household and farm characteristics are important in research and development project, particularly when the project intervenes with improved technological packaged. Household and farm characteristic are analyzed using descriptive approach by comparing and contrasting each characteristic across regions. Data were compiled from a field survey of 360 farmers during 2013-2014. The results show that every region has distinct characteristics. Vegetable farming was characterized by small-scale and fragmented farm. The land was closely situated around the home. Level of education was low. Being a farmer was the main occupation. Suitable policies related to these conditions should pay attention to the small-scale farming issues.